The effect of board links, audit partner tenure, and related party transactions on misstatements: Evidence from Chile - Sakthiharan Mahenthiran; Berta Silva Palavecinos; Hanns de la Fuente-Mella (International Journal of Financial Studies, 2020)
Companies restate when material misstatements are identified in previously issued financial statements. Misstatement research in Latin America is sparse, even though they are an important context to study this phenomenon. Chile's corporate governance regulations are considered exemplars for Latin American countries but its auditing profession is not well developed. Thus, Chile provides an interesting context to study the complementary roles of audit and board governance affecting misstatements. Using a sample of 104 Chilean listed firms over seven years, our study finds that the board links and audit partner tenure negatively affect misstatements. Specifically, given the prevalence of related party transactions (RPTs) in conglomerates, the finding suggests that cross directors monitor high-value RPTs, but that this is not a substitute for auditor expertise. The findings raise questions about the advisability of mandating audit partner rotation to strengthen auditor independence because the results indicate that a short audit partner tenure leads to the auditor not developing client-specific knowledge. The study makes contributions to the corporate governance literature by highlighting that board monitoring is not a good substitute for auditor monitoring of financial reporting integrity, and suggesting the need for having licensing requirements to become an auditor.
Keywords: G30; G38; G39; 330; corporate governance; audit governance; board independence; related party transactions; misstatements; financial reporting integrity